1979
DOI: 10.1080/08855072.1979.10668348
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Teachers’ Spanish Proficiency to Pupils’ Achievement

Abstract: To explore the relationship between teachers' proficiency in Spanish and their pupils' achievement, a test designed to measure the teachers' proficiency in Spanish was developed as part of a battery of tests for teachers in bilingual education programs -the CE RAS Teacher Tests for Spanish/English Bilingual Education. [Center for Educational Research at Stanford University -in addition to the Spanish proficiency test, the test battery includes tests on methods of teaching English and Spanish as a second langua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Ramírez and Stromquist (1979) found that teachers' knowledge about applied linguistics correlated significantly with pupils' learning of English as a second language. Teachers' proficiency in Spanish affected bilingual pupils' performance in language arts (Merino, Politzer, & Ramírez, 1979), and teachers' philosophy about reading greatly affected their methodology, particularly the manner in which oral reading errors were corrected among bilingual pupils in Wales, Spain, and the United States (Cortés, 1980).…”
mentioning
confidence: 99%
“…Ramírez and Stromquist (1979) found that teachers' knowledge about applied linguistics correlated significantly with pupils' learning of English as a second language. Teachers' proficiency in Spanish affected bilingual pupils' performance in language arts (Merino, Politzer, & Ramírez, 1979), and teachers' philosophy about reading greatly affected their methodology, particularly the manner in which oral reading errors were corrected among bilingual pupils in Wales, Spain, and the United States (Cortés, 1980).…”
mentioning
confidence: 99%
“…The increasing technical sophistication in bilingual education has given us im ortant information about specific features in bilin ual proummins 1979;Dulay and Burt 1978;ishman and Keller 1982;Legaretta 1979;Lewis 1977;Merino, Politzer, and Ramirez 1979;Trueba and Barnett-Mizrahi 1979). However, we still cannot satisfactorily account for the contradictions and confusion that surround many of the central issues in bilingual education.…”
mentioning
confidence: 99%